Investimento estrangeiro direto e crescimento econômico: aspectos teóricos e evidências empíricas para o Brasil - Freitas, Carolina (2019)
The Foreign Direct Investment (FDI) has been accompanying economic transformations since the second half of the twentieth century to contemporaneity. In 2017, Brazil was the fourth largest country to receive FDI in the world, being the first country with the largest inflow of FDI in Latin America. The objective of this research is to analyze the effect of economic growth on the attraction of Foreign Direct Investment (FDI) in Brazil, for the period 1975 to 2017. In order to evaluate the effects of economic growth on the FDI was used the Vector Error Correction Models (VECM) jointly Granger Causality Test and the Variance Decomposition. The variables used were FDI (Balance Of Payments Statistics) and nominal Gross Domestic Product (GDP), was obtained from the World Bank Data database. It was verified that the increase of 1% of the Brazilian economic growth increases the flows of FDI by 83,08% in Brazil. The results show that FDI causes, in the Granger causality, the economic growth and the attendance relation between the variables through the variance decomposition.